Dirichlet problem with Φ-Laplacian and mixed singularities - Rachůnková, I.; Stryja, J. (Нелінійні коливання, 2008)
We assume that A₁, A₂ ⊂ R are closed intervals containing 0, ϕ is an increasing odd homeomorphism with ϕ(R) = R and T ∈ (0,∞). We will study the singular Dirichlet problem of the form (ϕ(u' ))] + f(t, u, u' ) = 0 , u(0) = u(T) = 0, and we will prove the existence of its smooth solution satisfying u(t) ∈ A₁ , u'(t) ∈ A₂ for t ∈ [0, T]. Here f satisfies the Caratheodory conditions on the set (0, T) × D and can have time singularities at t = 0, t = T and space singularities at x = 0, y = 0 Для замкнених iнтервалiв A₁, A₂ ⊂ R, якi мiстять 0, та зростаючого непарного гомеоморфiзму ϕ, який задовольняє умови ϕ(R) = R i T ∈ (0,∞), вивчено сингулярну задачу Дiрiхле вигляду (ϕ(u'))' + f(t, u, u' ) = 0 , u(0) = u(T) = 0, i доведено iснування гладкого розв’язку, що задовольняє умови u(t) ∈ A₁ , u'(t) ∈ A₂ для t ∈ [0, T]. Тут f задовольняє умови Каратеодорi на множинi (0, T) × D i може мати особливостi в t = 0, t = T та просторовi особливостi в x = 0, y = 0.